Bio-waste derived fluorescent carbon dots based biodegradable mechanically strong hydrogel for stimuli-responsive nonsteroidal anti-inflammatory drug (NSAID) delivery - Sina M. Matalqah; Venkata Ramana Singamaneni; Patibandla Jahnavi; Umme Hani; Farhat Fatima; Rajeshwar Vodeti; Prem Shankar Gupta; Mohammad Badrud Duza; Md. Al Amin (PLoS ONE, 2026)
In this study, biowaste derived carbon dots (BCDs) were synthesized from sugarcane bagasse via a hydrothermal route and incorporated into biodegradable, mechanically robust hydrogels for stimuli-responsive nonsteroidal anti-inflammatory drug (NSAID) delivery. BCDs, characterized by FTIR, Raman spectroscopy, and photoluminescence analyses, exhibited abundant surface functional groups and excellent fluorescence properties. The integration of BCDs into the hydrogel matrix enhanced the mechanical strength, imparted pH-responsive drug release behavior, and maintained the structural integrity under physiological conditions. In vitro release studies using ibuprofen as a model drug demonstrated faster release under acidic conditions (pH 3.8) than under neutral and alkaline pH, aligning with pathological microenvironments. The drug release kinetics were best described by the Higuchi model, indicating a diffusion-controlled mechanism. Cytotoxicity assays confirmed the high biocompatibility of both free BCDs and BCD-loaded hydrogels, with sustained cell viability over five days. The combination of bio-derived nanomaterials, tunable release properties, and excellent cytocompatibility highlight the potential of this system for targeted and environmentally sustainable drug delivery applications. This approach provides a scalable and green route for developing advanced biomedical platforms from agricultural waste with significant implications for controlled drug release and tissue-compatible therapeutic interventions.